Embedded crack elements with non-uniform discontinuity modes - Manzoli, O. L.; Shing, P. B. (Springer, 2006)
The consequences of the use of embedded crack finite elements with uniform discontinuity modes (opening and sliding) to simulate crack propagation in concrete are investigated. It is shown the circumstances in which the consideration of uniform discontinuity modes is not suitable to accurately model the kinematics induced by the crack and must be avoided. It is also proposed a technique to embed cracks with non-uniform discontinuity modes into standard displacement-based finite elements to overcome the shortcomings of the uniform discontinuity modes approach.
Keywords: finite elements; embedded crack element; concrete fracture; material failure; non-uniform discontinuity modes; stress locking